Reduction procedure for obtaining solutions of the scalar additive Jump problem and Riemann boundary value problem in vectorial Clifford analysis - Carlos Daniel Tamayo Castro; Juan Bory Reyes; Ricardo Abreu Blaya (Wiley, 2024)
In this paper, we study existence of solutions to the scalar additive Jump problem and the Riemann boundary value problems in the context of vectorial Clifford analysis on domains with fractal boundaries. A reduction procedure is applied with great effectiveness to find the solution of the problems.
Keywords: Cauchy-Riemann and Dirac operators; Clifford analysis; fractal boundaries; Riemann boundary value problem